Kingdom of the Netherlands-Netherlands Antilles : Staff Report for the 2003 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation highlights that after a prolonged recession through the second half of the 1990s, the Netherlands Antilles economy has recently shown some important resilience. With the exchange rate pegged to the U.S. dollar, the Netherlands Antilles has enjoyed low inflation. With waning cost-push pressures related to higher energy costs and indirect tax increases, inflation has moderated to 0.5 percent in 2002. For 2003, inflation is projected to reach 2 percent in line with developments projected for the United States.